The formation and study of allogynogenesis Hemibarbus maculatus Bleeker - Yude Wang; An'min Liao; Chen Geng; Huifang Tan; Rurong Zhao; Shi Wang; Ming Wen; Kaikun Luo; Qinbo Qin; Chun Zhang; Min Tao; Shaojun Liu (Reproduction and Breeding, 2023)
Hemibarbus maculatus Bleeker (HM) is an economically important fish that is highly valued by consumers. Gynogenesis is an important breeding method in aquaculture that has been widely applied to many fish species. In this study, we adopted an improved method of gynogenesis that proceeds as follows: first, inactivated koi carp sperm were used to stimulate eggs of HM, and then the UV-inactivated koi carp (KOC) sperm and HM eggs were mixed and stirred for 20–30 s to activate the eggs. The activated eggs were placed in yellow mud at 0 °C for 20–22 min for cold shock treatment, and then placed in water at 4–6 °C, 8–10 °C, and 15–18 °C in order, each for 1–2 min. After incubation at 22–25 °C, gynogenetic Hemibarbus maculatus Bleeker (GHM) were obtained. Morphological measurements and blood cell comparisons showed that there were no significant differences between GHM and HM. At the molecular level, comparative analysis of microsatellites DNA indicated that one fragment of GHM came from the KOC. This study provides the first evidence that DNA fragments from male parents exist in GHM at the molecular level. This discovery has important implications for fish genetic breeding.